THE ROLE OF MUJAHADAH IN FORMING PARENTS' CHARACTER AS A PARENTING MEDIA - Ashshiddig, Mukhammad Fajrul Falah; Arofah, Asri; Fitriah, Ulfah; Fatihin, Moh. Khoirul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Family, as the smallest unit in public, plays a role in forming character children, and parents become educators first and foremost. Character-strong parents reflected in pattern care, interaction, and role models contributed to creating a morally noble generation. RA Masyitoh True, an Islamic education institution, uses the approach to build parents' character. Mujahadah, through spiritual efforts through worship, prayer, and self-control, aims to get closer to Allah SWT and develop positive attitudes and habits. Research This seeks to explore the effectiveness of implementation struggle in forming parent character as a parenting medium. With the qualitative descriptive, data was collected through observation, interviews, and documentation from the guardians of RA Masyitoh students True. Research results show that struggle increases spiritual awareness, control of self, patience, and responsibility of the parents. Besides that, activity tightens the emotional connection between parents and children and creates an environment of harmonious education. Implementing mujahadah, such as regular dhikr and prayer together, also impacts the formation of character children, especially in manners, morals, and attitudes towards teachers and parents. Research This confirms that struggle is a relevant and applicable approach. Development patterns fostered spirituality, which not only forms family sakinah, mawaddah, and mercy but also supports the creation of a character and pious generation.